Worship of Ancestors - Gendrolis, Edmundas (Problemos, 1996)
The ethnographic and archaeological material demonstrates that many peoples of Europe, Asia, Africa, Oceania and other countries practised worship traditions, celebrated festivities to the honour to the dead. Such worshiping had social functions and rational sense. The rituals to commemorate the dead linked the past and the present, generations and were a base for the existence of culture.